KEWENANGAN KANTOR PERTANAHAN DALAM MENYELESAIKAN SENGKETA OVERLAPPING PADA BIDANG TANAH: STUDI DI KABUPATEN KUNINGAN - Budiman, Haris; Firdansyah, Muhammad Faldi (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Overlapping or multiple certificates occur because there are two certificates on the same land and are officially issued by the National Land Office. As a result this overlap raises a dispute between the parties, and then the certificate is no longer valid evidence. The formulation of the problem is the regulation of overlapping dispute resolution according to legislation in Indonesia and how the authority of the Land Office in resolving disputes overlapping land parcels. The research method used is empirical juridical using primary and secondary data. The results showed that there is no specific regulation regarding disputes over double or overlapping certificates, currently the regulations used by the District Land Office still refer to the Regulation of the Minister of Agrarian Affairs and Spatial Planning number 11 of 2016 concerning Settlement of Land Cases. To reinforce the authority of the Land Office in resolving cases of multiple certificates, a special regulation on the settlement of overlapping land cases is needed. The conclusion shows that the Land Office has carried out its role by its duties, principal, and functions, but because the regulations used are general, many obstacles are found in solving the problem of multiple certificates, therefore there is a need for legal reform and education from the government to the public about the importance of officially registering land.